More on the influence of gender equality on gender differences in economic preferences - Sara Cerioli; Andrey Formozov (Journal of Economics and Statistics, 2024)
This study replicates and extends the work of Falk and Hermle (2018. “Relationship of Gender Differences in Preferences to Economic Development and Gender Equality.” Science 362 (6412): eaas9899), who hypothesized that gender differences in economic preferences (patience, altruism, willingness to take risks, negative and positive reciprocity, and trust) were related to economic development and gender equality. While we were able to replicate their main results, we found that a number of methodological choices called for reexamination. Specifically, the use of an ad hoc gender equality index built by the authors lacked systematic justification, which led us to employ solely well-established indexes from gender studies in the subsequent analysis. This new analysis confirmed a positive and statistically significant association between aggregated gender differences in economic preferences and economic development conditional on gender equality. However, in contrast to the original article, the evidence of the relationship between gender differences and gender equality conditional on economic development was weak. We also investigated the relationships for the separate economic preferences and found that economic development predicts gender differences in all six preferences, whereas gender equality seems to have a negligible or null influence on most of them. Our findings provide a more nuanced view of the gender differences in economic preferences, with possible implications for policy-making.
Keywords: C19; D01; C91; D63; D64; D81; F0; 330; cross-country variation; economic preferences; gender differences; replication study